(untitled) (Bombay Hospital Journal, 2026)
Introduction: Hypertension is a common non-communicable disease and is of major public health concern accounting for 19% of all deaths globally. The lack of awareness about hypertension is a major contributory factor for the delayed diagnosis of asymptomatic cases, thus being labeled as a “silent killer disease.” Effective control of blood pressure is a must and for achieving it, a long-acting antihypertensive agent is required. Telmisartan is one of the angiotensin II receptor blockers whereas cilnidipine is a novel calcium antagonist. Cilnidipine has shown prolonged and desirable antihypertensive effects. The present questionnaire-based study conducted on various clinicians across different parts of the country analyses the pattern of patients with hypertension and other comorbidities in their clinical practice along with the trend in the prescription of antihypertensives either mono and/or combination therapy. Materials and Methods: The present study is a questionnairebased cross-sectional study consisting of 25 validated structured questions. The study was approved by the Institutional Ethical Committee. All the completed forms were included in the study whereas incomplete form was excluded from the study. Observation and Results: The survey reflects that 87% of the patients have diabetes mellitus as one of the most common comorbid conditions associated with hypertension. About 86.5% of the clinicians (86.5%) are of the opinion that more than 30% of the patients required combination therapy of telmisartan and cilnidipine with the addition of diuretics in uncontrolled hypertension. The combination also offers many other benefits such as its anti-atherosclerotic properties and endorgan protection. Conclusion: The study highlights that combination therapy is very effective in treating hypertension even if associated with other comorbid conditions such as diabetes and chronic kidney disease.